First moves how to start a chess game - Pritchard, David
First Moves is an opening primer for the complete novice. It offers clear, simple advice on how to start a game of chess playing either as white or black. It is a book to be read, not studied. When both sides are locked in combat, it is easy to find plans. But at the beginning, signposts are few. Why move one man instead of another? First Moves will help you make the right decisions, improve your game and get you thinking straight. First Moves assumes no more than a knowledge of the rule of chess. It ends where other opening books begin